1966
DOI: 10.1111/j.1365-2621.1966.tb01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins of the Garden Huckleberry, Solanum guineese

Abstract: SUMMARY The anthocyanin pigments of the garden huckleberry (Solanum guineese) were isolated and identified from their chromatographic, spectral and chemical properties. The major pigment was petanin (petnnidin‐3 (p‐coumaroyl rutinoside)‐5‐glucoside) (93%). The minor pigments were petunidin‐3‐rutinoside‐5‐glucoside (3.5ys), negretein (malvidin‐3 (p‐coumaroyl rutinoside)‐5‐glucoside (2.0%), and a new compound, guineesin, petunidin‐3‐rutinoside‐5‐glucoside acylated with two molecules of p‐coumaric acid (1.5%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The results of the analyses optimized for petunidin-3-(p-coumaroyl rutinoside)-5-glucoside confirmed the differences between the two groups and showed that the 'german' accessions contained remarkable high anthocyanin concentrations of 8.1-13.9 g kg À1 which were higher than those of Blueberries (1.09-2.61 g kg À1 ) or Grape (0.03-7.50 g kg À1 ) and at a similar level as that of Aroniaberries (2.00-10.00 g kg À1 ) and Elderberries (3.61-12.66 g kg À1 ) (Jansen and Flamme 2006). In the first report about anthocyanins of Solanum scabrum, Francis and Harborne (1966) found approximately 0.1% total pigment concentration of the fresh weight and concluded that the berries are appropriate as colorants. It should be emphasized that the pigment yields of the 'german' accessions calaculated as percent of the fresh weight were in the range of 0.8-1.3% and exceeded clearly the value reportet by Francis and Harborne (1966).…”
Section: Anthocyanin Concentrationsmentioning
confidence: 79%
See 4 more Smart Citations
“…The results of the analyses optimized for petunidin-3-(p-coumaroyl rutinoside)-5-glucoside confirmed the differences between the two groups and showed that the 'german' accessions contained remarkable high anthocyanin concentrations of 8.1-13.9 g kg À1 which were higher than those of Blueberries (1.09-2.61 g kg À1 ) or Grape (0.03-7.50 g kg À1 ) and at a similar level as that of Aroniaberries (2.00-10.00 g kg À1 ) and Elderberries (3.61-12.66 g kg À1 ) (Jansen and Flamme 2006). In the first report about anthocyanins of Solanum scabrum, Francis and Harborne (1966) found approximately 0.1% total pigment concentration of the fresh weight and concluded that the berries are appropriate as colorants. It should be emphasized that the pigment yields of the 'german' accessions calaculated as percent of the fresh weight were in the range of 0.8-1.3% and exceeded clearly the value reportet by Francis and Harborne (1966).…”
Section: Anthocyanin Concentrationsmentioning
confidence: 79%
“…In the first report about anthocyanins of Solanum scabrum, Francis and Harborne (1966) found approximately 0.1% total pigment concentration of the fresh weight and concluded that the berries are appropriate as colorants. It should be emphasized that the pigment yields of the 'german' accessions calaculated as percent of the fresh weight were in the range of 0.8-1.3% and exceeded clearly the value reportet by Francis and Harborne (1966).…”
Section: Anthocyanin Concentrationsmentioning
confidence: 98%
See 3 more Smart Citations